Functional outcome of elastic intramedullary nailing for femoral shaft fractures in children - Mahmood, Hamid Ahmed; Abdulqader, Sarkan Ahmed (Sulaimani Journal for Pure and Applied Sciences, 2022)
Background: Pediatric femoral shaft fracture is the most frequent fracture type in orthopedic practice in which males are affected more commonly than females. Currently, intramedullary fixation for the managing of femoral shaft fracture in children is widely used worldwide, including Iraq, which overcomes most of the difficulties related to other treatment modalities. Objectives: This study aimed to determine the clinical, functional, and radiological consequences of pediatric femoral shaft fractures achieved with a titanium elastic nail system (TENS). Materials & Methods: In this study, 28 children aged 5-10 years with femoral shaft fracture admitted to Shar Hospital, Sulaimaniyah, Republic of Iraq, were enrolled. Their fractures were fixed with Titanium Elastic Nail (TEN), in which a pair of the same-sized nail was used for each fracture. The outcomes were assessed using Flynn’s scoring criteria. Finally, the patients were discharged the next day and followed up after 2, 4, 8, 12 and 20 weeks of surgery. Results: Based on Flynn’s score assessment, the outcome of 85.71% of patients were excellent, 12.5% were satisfactory, and 1.79% were poor. All patients were showed a radiological unification and a conceivable full weight-bearing in a mean time of ~ 9 weeks, while their full knee variety of movement was attained in 2 months. Conclusions: TENS is a potential means to treat femoral shaft fractures in children as it is a simple, safe, minimally invasive, and physeal-protective with fewer complications and a high rate of good and excellent outcomes.
Keywords: Femoral shaft fracture; pediatric cases; titanium elastic nailing system; manageable outcomes